2016
DOI: 10.2196/jmir.5409
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Treatment Switching in Multiple Sclerosis Therapies in US Patients Active on Social Media: Application of Social Media Content Analysis to Health Outcomes Research

Abstract: BackgroundSocial media analysis has rarely been applied to the study of specific questions in outcomes research.ObjectiveThe aim was to test the applicability of social media analysis to outcomes research using automated listening combined with filtering and analysis of data by specialists. After validation, the process was applied to the study of patterns of treatment switching in multiple sclerosis (MS).MethodsA comprehensive listening and analysis process was developed that blended automated listening with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Finally, while people were getting medicine and treatment suggestions from family members or friends for their illnesses in the past, today, it seems that online resources and social media are the routes people use when searching for medicine and treatment (De Martino et al, 2017;Risson et al, 2016). Moreover, since individuals direct their attention to new communication channels instead of e-mail or telephone, sector representatives should use social media more actively by informing patients about encountered health-related problems and sharing useful health-related strategies through social media.…”
Section: Figure 2: Results Of Path Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, while people were getting medicine and treatment suggestions from family members or friends for their illnesses in the past, today, it seems that online resources and social media are the routes people use when searching for medicine and treatment (De Martino et al, 2017;Risson et al, 2016). Moreover, since individuals direct their attention to new communication channels instead of e-mail or telephone, sector representatives should use social media more actively by informing patients about encountered health-related problems and sharing useful health-related strategies through social media.…”
Section: Figure 2: Results Of Path Analysismentioning
confidence: 99%
“…Moreover, compared to previous years, there are more conscious patient profiles about services and illnesses through changes in technology, including online platforms, which enable interactions about various health topics related to informing patients (Househ et al, 2014). In parallel, the Internet has been the first source of information used by many patients (Hesse et al, 2010;Risson et al, 2016). Thus, patients can evaluate and compare the given health service, or they can get more information about the illness through different online resources, such as social media, before even taking the offered service.…”
Section: Introductionmentioning
confidence: 99%
“…The immediacy of these data, along with their widespread availability, could provide insights into adverse effects and noncompliance. Indeed, social listening can be used to track the most-common reasons for patients switching between therapies [65]. It has the potential to provide a large amount of information about 'real-world benefit' as discussed from the patient's perspective [66].…”
Section: Rwd and Social Listeningmentioning
confidence: 99%
“…One innovative method that can help ensure this information is captured is social media listening. With the correct structure and context, social media listening can provide insights into patient characteristics, treatment satisfaction, treatment switching, reasons for switching and much more [9]. Studies capturing this patient-reported data can be extended by linking data from claims and electronic medical record data systems to obtain a more complete picture [10].…”
Section: Patient-reported Outcomesmentioning
confidence: 99%